Peran Motivasi Kerja Dalam Memediasi Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan: Studi Pada Karyawan Di Wilayah Kemayoran - Nur Zaidah; Agung Solihin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to determine the role of work motivation in mediating the influence of leadership style and organizational culture on employee performance. This study uses primary data by distributing questionnaires to employees of an organization in the Kemayoran area, Central Jakarta. Sampling was done using simple random sampling. This research was using samples of as many as 100 respondents. The data analysis method used as Partial Least Square (PLS)- SEM with the help of the data analysis tool SmartPLS 3.0. The result of this research shows leadership style and organizational culture have a positive effect on work motivation. Leadership style has no effect on employee performance. Organizational culture and work motivation have a positive effect on employee performance. Work motivation mediates and intervenes in the influence of leadership style on employee performance. Work motivation mediates and intervenes in the influence of organizational culture on employee performance